Western Scotia Sea margins: Improved constraints on the opening of the Drake Passage - Lodolo, Emanuele; Donda, Federica; Tassone, Alejandro Alberto (Journal of Geophysical Research: Solid Earth)
We present a revised tectonic interpretation (from ∼28 Ma to 3.2 Ma) of the western sector of the Scotia Sea, incorporating new multichannel seismic reflection profiles and magnetic anomaly identifications for the continental margin off the Tierra del Fuego Island, and available complementary data for the conjugate margin of the northwestern flank of the South Scotia Ridge. Seismic profiles show a remarkable diversity of the pair of conjugate passive margins of the western Scotia Sea in both their morphology and structural framework. The Tierra del Fuego continental margin can be related to a classic rifted passive margin, while the southwestern margin of the Scotia Sea is characterized by steep slopes mostly generated by subvertical faults that abruptly separate the continental crust of the South Scotia Ridge from the oceanic crust of the western Scotia Sea. This structural difference was caused by intense strike-slip tectonism, mostly concentrated along the modern South Scotia Ridge since the early development of the western Scotia Sea. We find evidence for a previously unrecognized magnetic anomaly 10 (∼28 Ma) at the foot of the Tierra del Fuego continental margin; the same anomaly is present at the conjugate northern flank of the South Scotia Ridge. The timing of events leading to the earliest development of the western Scotia Sea, which determined the opening of the Drake Passage is important because this gateway opening had a profound effect on global circulation and climate. The thickness and the distribution of the sedimentary cover overall in the abyssal plain off the two western Scotia Sea margins is different. This is due to the different regimes of the bottom-current flows which affected the western Scotia Sea, both in the past and in the present time. Fil: Lodolo, Emanuele. Istituto Nazionale di Oceanografia e di Geofisica Sperimentale; Italia Fil: Donda, Federica. Istituto Nazionale di Oceanografia e di Geofisica Sperimentale; Italia Fil: Tassone, Alejandro Alberto. Consejo Nacional de ...